A descriptive study of bone density based on angle’s malocclusion classification on female patients aged 13–30 years old on panoramic radiograph - Pei C. Ling; Ria N. Firman; Farina Pramanik (Journal of Dentomaxillofacial Science, 2017)
Objective: This study was performed to determine the bone density based on angle’s malocclusion classification on female patients aged 13–30 years old using panoramic radiograph.Material and Methods: Ninety digital panoramic radiographs of female patients aged 13–30 years old and with 30 radiographs representing each of the angle’s malocclusion classes (class I, class II, class III) were used. The bone density was measured by using ImageJ software with 20 x 20 pixels intensity by using a method based on the mental index (MI).Results: The mean bone density of female patients aged 13–30 years old with angle’s malocclusion of class I was 18.726% of cortical and 81.274% of marrow, class II was 16.804% of cortical and 83.196% of marrow, and class III was 15.911% of cortical and 84.089% of marrow.Conclusion: The bone density of female patients aged 13–30 years old with angle’s class I malocclusion was higher than class II and class II malocclusion had higher bone density than class III on panoramic radiograph.